International trade war - Spice Road against Silk Road - Joon Seok Oh (International Trade, Politics and Development)
Purpose – The purpose of this paper is to analyse the international political economy of Korea and its effects due to geopolitical tension between China and the USA. Design/methodology/approach – Economic war between China and the USA has prolonged longer than expected. Aftermath of the COVID-19 pandemic, reforming the supply chain has been the centre of economic tension between China and the USA. Quite recently, with the rapid expansion of Chinese e-commerce platforms, distribution channels come upon a new economic tension between the two. And now is the time to pivot its pattern of conflict from competition into cooperation. In this end, economic diplomacy could be a useful means to give a signal of cooperation. From the view of economic diplomacy, this paper tries to analyse the projected transition of economic war between China and the USA with its implication on the trade policy of Korea. Findings – As an implementation of economic diplomacy, China suggested the Belt and Road Initiative (BRI), enhancing trade logistics among related countries to gain competitiveness. In 2023, the Biden administration suggested the India-Middle East and Europe Economic Corridor as a counter to BRI, which will be a threshold for changing trade policy from economic war into economic diplomacy. As a result, it is expected China and the USA will expand their economic diplomacy in a way to promote economic cooperation among allied states, while the distribution channel war would continue to accelerate the economic tension between China and the USA. Korea has to prepare for and provide measures handling this geopolitical location in its trade policy or economic diplomacy. Originality/value – This research contributes to the awareness and understanding of trade environments from the perspective of economic diplomacy.